Market-based approaches to food safety and animal health interventions: Lessons from smallholder pig value chains in Vietnam - Rich, Karl M.; Huyen Nguyen, Thi-Thu; Ha Duong-Nam; Hung Pham Van; Nga Nguyen Thi Duong; Unger, Fred; Lapar, Ma. Lucila (Lincoln University, 2015)
Food safety and animal health issues are increasingly important constraints to smallholder pig production in Viet Nam. Recent studies have highlighted the significant prevalence of animal disease and food‐borne pathogens inherent within the Vietnamese pig sector. These in turn have important negative livelihoods effects on smallholder pig producers and other value chain actors, as well as important public health impacts. An important research gap is in identifying ex‐ante appropriate market‐based policy responses that take into account the tradeoffs between improved animal health and food safety outcomes and their associated costs for different value chain actors as a means of developing chain‐level solutions for their control. In this paper, we constructed a system dynamics model of the pig value chain that combines a detailed model of herd production and marketing with modules on short‐ and long‐term investment in pig capacity, and decisions by value chain actors to adopt different innovations. The model further highlights the feedbacks between different actors in the chain to identify both the potential entry points for upgrading food safety and animal health as well as potential areas of tension within the chain that may undermine uptake. Model results demonstrate that interventions at nodal levels (e.g. only at farm or slaughterhouse level) are less cost‐effective and sustainable than those that jointly enhance incentives for control across the value chain, as weak links downstream undermine the ability of producers to sustain good health practices.